Serum IL-6 and IL-10 concentrations in bitches with pyometra undergoing ovariohysterectomy - Dąbrowski, Roman (Acta Vet Scand, 2015)
BACKGROUND: Pyometra is a serious bacterial infection of the uterus affecting female dogs and manifests as an accumulation of pus in the uterine lumen. The aim of the study was to assess changes in serum interleukin (IL)-6 and IL-10 concentrations in bitches with pyometra undergoing ovariohysterectomy. FINDINGS: Blood samples were collected from healthy bitches (controls) and bitches with pyometra before surgery, and 3 and 10 days after ovariohysterectomy. Before surgery, bitches with pyometra had significantly higher serum concentrations of IL-6 and IL-10 than the controls. After surgery, the serum concentration of IL-6 and IL-10 decreased significantly. In healthy dogs, the concentration of IL-6 and IL-10 showed a significant increase 3 days after surgery followed by a decrease on day 10. CONCLUSION: An increase in serum concentrations of IL-6 and IL-10 was present before surgery in bitches with pyometra and 3 days after ovariohysterectomy in healthy controls. Concentrations decreased after ovariohysterectomy and/or proper healing, suggesting that these cytokines can be useful for assessment of the postoperative period in bitches.